Factors Influencing Educational Leadership and Management Processes in Omani Higher Education Institutions: A Qualitative Study - Al Maqbali, Salim Bati (Dirasat: Educational Sciences, 2024)
Objectives: This study aims to explore the factors influencing leadership and administrative processes in Omani higher education institutions from the perspective of faculty members. Methods: The study adopted a qualitative approach, involving interviews with 14 faculty members from various colleges at the University of Technology and Applied Sciences. In-depth interviews were conducted with all participants to gather essential information on the impact of organizational structure and administrative practices. Results: The study revealed that the hierarchical and centralized organizational structure of the university and its colleges poses a barrier to effective college management. This structure limits the deans' ability to make decisions quickly and efficiently, leading to delays in administrative processes and the loss of some important opportunities. Although the quality assurance system has contributed to improving certain aspects of administrative work in the colleges, there are still areas in need of development, such as the automation of administrative processes. Additionally, the study showed that there is a clear societal influence on administrative decisions within the colleges, which adds pressure on management to adjust certain decisions to align with societal expectations, often in conflict with the university’s hierarchical system. Conclusions: The study’s findings highlight an urgent need to review and develop the organizational structures and administrative processes in Omani higher education institutions to enhance management efficiency and support academic progress. This would better meet faculty members' aspirations and address current challenges.